If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+6=-2(x+3)+12
We move all terms to the left:
4x+6-(-2(x+3)+12)=0
We calculate terms in parentheses: -(-2(x+3)+12), so:We get rid of parentheses
-2(x+3)+12
We multiply parentheses
-2x-6+12
We add all the numbers together, and all the variables
-2x+6
Back to the equation:
-(-2x+6)
4x+2x-6+6=0
We add all the numbers together, and all the variables
6x=0
x=0/6
x=0
| 3y+4=27 | | 3(4x+12)=180 | | n−35=26 | | (7x+15)+(8x+15)=180 | | u−25=7 | | 2q=78 | | 3=y4 | | (3x+5)+(12x+25)=90 | | 4y²+16y+15=0 | | 1/4y-10=1/7y | | 2(−3x+4)=5x+2 | | 38 = n12 | | 2x-6=2x=-6 | | 3x-4-x=2x-6 | | -8r=65 | | 4x+(3x+7)=180 | | a²+8a=-15 | | 124x=180 | | x+x*x=72 | | -15t^2-23t+28=0 | | 5x*20=70 | | 2-3x=x=10 | | -17-m=-59 | | 4z+1=3-2z | | (X-7)+90+(2x+16)=180 | | 5x(20)=70 | | x/162x+1=128 | | 4^4x+2-5*2^4x-1+1=0 | | 5.2=12t-4.9t^2 | | 8y-9=-9 | | -0.025x=-16 | | 141000000÷x=1.14 |